2013
DOI: 10.1007/s10895-013-1162-5
|View full text |Cite
|
Sign up to set email alerts
|

Consequential secondary structure alterations and aggregation during prolonged casein glycation

Abstract: Non-enzymatic glycosylation (glycation) of casein is a process used not just to ameliorate the quality of dairy products but also to increase the shelf life of canned foods, including baby milk supplements. Incubation of κ-casein with reducing sugars for 15 days at physiological temperature showed the formation of a molten globule state at day 9 and 12 during fructation and glucation respectively. This state exhibits substantial secondary structure and maximum ANS binding. Later on, glycation resulted in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
6
14
0
Order By: Relevance
“…The ribosylation is responsible for the conformational changes, leading to an increase in total β-conformation, particularly the excess increases in the formation of intermolecular beta-sheet structures. This was consistent with the results of glycated albumin due to the conformational change from its native α-helical to β-sheeted structures [64][65], resulting in the formation of protein aggregation and fibrillation [65][66][67][68].…”
Section: The Curve-fitted Amide I Band Of Native Hsa or Hsa-ribose Misupporting
confidence: 91%
“…The ribosylation is responsible for the conformational changes, leading to an increase in total β-conformation, particularly the excess increases in the formation of intermolecular beta-sheet structures. This was consistent with the results of glycated albumin due to the conformational change from its native α-helical to β-sheeted structures [64][65], resulting in the formation of protein aggregation and fibrillation [65][66][67][68].…”
Section: The Curve-fitted Amide I Band Of Native Hsa or Hsa-ribose Misupporting
confidence: 91%
“…6 it is possible to conclude that a-LaeLys supramolecular structures prepared at both pH values (i.e. pH 3 and 11), when treated at 25 C for 15 and 35 min, maintained the overall characteristics expected for an a-helix-rich protein structure (Greenfield, 1999;Jindal & Naeem, 2013) e Fig. 6a and b.…”
Section: Circular Dichroismmentioning
confidence: 80%
“…The native spectrum of a-La and Lys exhibited a negative peak at 208 nm (more prominent) and a large band with negative ellipticity intensity at ca. 222 nm indicating that the secondary structures of those proteins are rich in a-helices (Greenfield, 1999;Jindal & Naeem, 2013); however native a-La displayed a peak with higher negative signal intensity than Lys. A similar behavior was found by He et al (2013) for native a-La and Lys prepared at 1.5 mg mL À1 , by Diniz et al (2014) for native a-La, prepared at 1.5 mg mL À1 and by Bob aly et al (2014) for native Lys prepared at 2.3 mg mL À1 ; these authors observed negative peaks at approximately 208 and 222 nm, which are typical of well-defined a-helix-rich proteins.…”
Section: Circular Dichroismmentioning
confidence: 99%
“…In addition, an increase in peak emission intensity was observed. These findings indicate that the surrounding chemical environment of the chromophores became more apolar (Jindal & Naeem, 2013;Taheri-Kafrani, Asgari-Mobarakeh, Bordba, & Haertlé, 2010;Taheri-Kafrani, Bordbar, Mousavi, & Haertlé, 2008;Zhang, Qi, Zheng, Li, & Liu, 2009), suggesting that during the interaction between α-la and GMP molecules, the chromophores remain buried deeper in the core structures composed of these molecules ( Fig. 4a and b).…”
Section: Fluorescence Spectroscopymentioning
confidence: 91%